2016
DOI: 10.1038/mp.2016.150
|View full text |Cite
|
Sign up to set email alerts
|

MiR-137: an important player in neural development and neoplastic transformation

Abstract: MicroRNAs (miRNAs) represent an important class of small regulatory RNAs that control gene expression posttranscriptionally by targeting mRNAs for degradation or translation inhibition. Early studies have revealed a complex role for miRNAs in major biological processes such as development, differentiation, growth and metabolism. MiR-137 in particular, has been of great interest due to its critical role in brain function and putative involvement in the etiology of both neuropsychiatric disorders and cancer. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(135 citation statements)
references
References 141 publications
2
126
0
Order By: Relevance
“…MicroRNAs (miRNAs) are small, endogenous, noncoding RNAs that negatively regulate gene expression at the post‐transcriptional level by binding to the “seed region” located in the 3’‐untranslated region (3’‐UTR) of their target mRNA (Mahmoudi & Cairns, ). MiRNAs are considered as a group of regulators in various biological processes, such as cell proliferation, differentiation, apoptosis, and cycle regulation (Bhaskaran et al, ; Mansini et al, ; Nowakowski et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are small, endogenous, noncoding RNAs that negatively regulate gene expression at the post‐transcriptional level by binding to the “seed region” located in the 3’‐untranslated region (3’‐UTR) of their target mRNA (Mahmoudi & Cairns, ). MiRNAs are considered as a group of regulators in various biological processes, such as cell proliferation, differentiation, apoptosis, and cycle regulation (Bhaskaran et al, ; Mansini et al, ; Nowakowski et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some epidemiological researches have reported the negative association between AD and cancer, which means older persons with AD dementia have a reduced risk of cancer and vice versa (Calderwood & Murshid, 2017;Nixon, 2017;Shafi, 2016). Following studies have demonstrated that many factors, including miRNAs, are involved in the inverse relationship between AD and cancer (Nagaraj, Zoltowska, Laskowska-Kaszub, & Wojda, 2019 MicroRNAs (miRNAs) are small, endogenous, noncoding RNAs that negatively regulate gene expression at the post-transcriptional level by binding to the "seed region" located in the 3'-untranslated region (3'-UTR) of their target mRNA (Mahmoudi & Cairns, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…miR‐137 is located on human chromosome 1p22 and is involved in many biological processes and diseases . To date, research indicates that miR‐137 may play a dual role during tumorigenesis, and that the nature of this role may be dependent on tumor type and target messenger RNA (mRNA) identities .…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs were predicted to regulate 20%‐30% of human genes . The involvement of miRNAs in many aspects of psychiatric disorder makes them potential candidates as biomarkers or targets for clinical diagnosis and treatment . Although the importance of miRNAs in brain functions has been well‐documented, more efforts are required to understand the full extent of miRNA regulatory mechanism and their pathological effects in neuropsychiatric disorders.…”
Section: Perspective Of Mirna Therapiesmentioning
confidence: 99%
“…147,148 The involvement of miRNAs in many aspects of psychiatric disorder makes them potential candidates as biomarkers or targets for clinical diagnosis and treatment. 6,7,9,149 Although the importance of miRNAs in brain functions has been welldocumented, more efforts are required to understand the full extent of miRNA regulatory mechanism and their pathological effects in neuropsychiatric disorders. The first challenge remained is to identify functional miRNAs located in human genome associated with schizophrenia.…”
Section: Per S Pec Tive Of Mirna Ther Apie Smentioning
confidence: 99%